Paradoxical Reactions to Anti-TNFα and Anti-IL-17 Treatment in Psoriasis Patients: Are Skin and/or Gut Microbiota Involved? - Jiraskova Zakostelska, Zuzana; Reiss, Zuzana; Tlaskalova-Hogenova, Helena; Rob, Filip (Dermatology and therapy, 2023)
Psoriasis is a chronic, immune-mediated, inflammatory disease primarily affecting the skin. It is currently coming to light that patients with psoriasis have disrupted intestinal barrier and often suffer from comorbidities associated with the gastrointestinal tract. Moreover, there is growing evidence of both cutaneous and intestinal paradoxical reactions during biologic treatment in patients with psoriasis. This review focuses on barrier defects and changes in immune responses in patients with psoriasis, which play an important role in the development of the disease but are also influenced by modern biological treatments targeting IL-17 and TNFα cytokines. Here, we highlight the relationship between the gut-skin axis, microbiota, psoriasis treatment, and the incidence of paradoxical reactions, such as inflammatory bowel disease in patients with psoriasis. A better understanding of the interconnection of these mechanisms could lead to a more personalized therapy and lower the incidence of treatment side effects, thereby improving the quality of life of the affected patients.
Keywords: Gut microbiota; Skin adverse events; IL-17; Biologics; Psoriasis; Skin microbiota; Gut–skin axis; IBD; TNFα